A Critical Review of the Book Conjugation 2 with a Descriptive Analysis Approach - Zohreh Ghorbani Madavani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Textbook criticism is of great importance and status. The book “Conjugation 2”, written by Ahmad Pashazanoos, while addressing issues related to the name, has tried with exercises at the end of each lesson to provide the audience with the opportunity to explore the material presented in practice. This book is a continuation of the book “Conjugation 1” by the same author. The present article critiques the two levels of form and content of this book by descriptive-analytical method and relying on the descriptive analysis approach. All the strengths and weaknesses of the book in the two areas of form, content and mistakes of the author have been pointed out by presenting documents and examples of the book. Finally, in general, this book can be called a scientific package that tries to provide inflectional content by deductive method (mentioning the rule and then providing an example witness( and the role of meaning and subtle semantic differences in different inflectional forms are insignificant.